Explaining structural change in cardiovascular mortality in Ireland 1995 - 2005: A time series analysis - Richard Layte; Sinead O'Hara; Kathleen Bennett (The Economic and Social Research Institute (ESRI), 2009)
Background: Deaths from circulatory respiratory causes among older age groups in Ireland fell sharply between 1995 and 2005 as did the seasonality of deaths from these causes.Objective:To examine whether a structural break has occurred in deaths from circulatory causes in Ireland between 1995 and 2005 and test whether this can be explained by changes in the prescribing of cardiovascular medications during the same period controlling for weather trends. Methods: Grouped logit Time series models were used to identify if and at which quarter a structural break occurred in Irish circulatory deaths between 1995 and 2005. Data on cardiovascular prescribing and temperature within the quarter were entered into the trend-break model to examine whether the structural break could be explained. Results: There was a reduction in circulatory deaths of 0.82%/quarter among men 1995-2005 which increased by 0.5%/quarter after the final quarter of 1999. The 25% excess winter deaths among men fell by 9% after Q4 1999. Among women the long term decline in deaths of 0.53%/quarter increased by 0.48% after Q1 2000 and seasonality was reduced by 6.8%. The structural break in trend and seasonality was higher among those aged 85+. Controlling for temperature, beta-blocker, ace-inhibitor and aspirin medications rendered the structural break indicator insignificant among all age groups for men. Diuretic, statin and calcium channel blocker medications could not explain the break point for men aged 75 to 84. Beta blocker, aspirin and calcium channel blocker medications explained mortality trends among all age groups among women. Ace inhibitor and statin could not explain trends amongst women aged 65-74 and nitrates and diuretics did not explain trends for any age group. Conclusions: Models suggest that cardiovascular prescribing significantly reduced circulatory mortality among men and women aged 65+ after 1999 in Ireland but the effect of prescribing was lower among women than men. Beta-blocker, ace inhibitor and aspirin medications were more successful than statin, diuretic and nitrates at explaining trends.
Keywords: 330; Sterblichkeit; Herzkrankheit; Zeitreihenanalyse; Irland